(untitled) (Research, Society and Development, 2022)
General purpose: To describe the incidence and profile of the population affected by stroke admitted to the adult intensive care unit (ICU) of a Public Hospital in the city of São Paulo. Methods: Cross-sectional, quantitative, analytical and prospective research. Data collection performed through a questionnaire, information from medical records and completed by the patient or guardian. The sample selected for convenience, composed of 21 individuals hospitalized in the ICU with a diagnosis of stroke, from august to october 2021. Results: 261 patients were hospitalized, 21 (8.17%) with a diagnosis of stroke; 14 (66.67%) with EVA, male (57.14%), 7 (33%) with EVA, female (57.14%), both were prevalent in people over 60 years old (76%), of the white race (61%). 61% of patients with previous health follow-up, prevalent in the public health service (85%). The highest demand for health service prior to hospitalization was the IS (64.28%). Among the strokes, 18 had comorbidities (SAH 66.67%, smoking 42.46%, DM 33.33%, heart disease 19.05%) and 83% were previously treated. Regarding the knowledge that comorbidities can lead to CVA, 52.38% knew about the subject. EVA with 85.71% of discharge and EVA 57.14% of death. The average hospitalization days were: AVEI 24.64 days and AVEH 14.14 days. Conclusion: This research found trends in accordance with the literature, showing the incidence of ischemic stroke, susceptible in people over 60 years of both sexes, with one or more CNCDs, and it has evidenced the importance of RAS to the health care system.